2012
DOI: 10.1080/09064702.2013.773056
|View full text |Cite
|
Sign up to set email alerts
|

Using strains of Propionibacteria to mitigate methane emissionsin vitro

Abstract: Sixteen strains of propionibacteria were inoculated into in vitro ruminal incubations to evaluate their potential to reduce methane (CH 4 ) production from concentrate and forage diets. Propionibacterium freudenreichii T114, Propionibacterium thoenii T159, and Propionibacterium thoenii ATCC 4874 lowered (p B0.05) CH 4 production from both substrates compared to control. Compared to control, Propionibacterium jensenii T1, Propionibacterium freudenreichii T31, and Propionibacterium freudenreichii T54 lowered (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 40 publications
1
24
3
Order By: Relevance
“…Animals used in the present study had no previous exposure to Propionibacterium strains thereby ruling out the possibility of any carry-over effects that might have confounded results in the present study. The present in vivo study showed no significant treatment effects on total CH 4 production for any of the strains used, in contrast to observations from a previous in vitro study (Alazzeh et al 2013). Moreover, total enteric CH 4 emissions corrected for DM and gross energy intake tended to be greater with the inoculation of Propionibacterium strains.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…Animals used in the present study had no previous exposure to Propionibacterium strains thereby ruling out the possibility of any carry-over effects that might have confounded results in the present study. The present in vivo study showed no significant treatment effects on total CH 4 production for any of the strains used, in contrast to observations from a previous in vitro study (Alazzeh et al 2013). Moreover, total enteric CH 4 emissions corrected for DM and gross energy intake tended to be greater with the inoculation of Propionibacterium strains.…”
Section: Discussioncontrasting
confidence: 93%
“…However, no effects were observed on total CH 4 emissions due to low persistency of the inoculated strains. Contrary to the previous in vivo studies (Vyas et al 2014a(Vyas et al , 2014b, in vitro batch culture studies with Propionibacterium strains showed promising results with significant reduction in CH 4 production using both high-forage and high-grain diets (Alazzeh et al 2013). The discrepancy between studies might be related to different strains of Propionibacteria used in the in vitro batch culture experiment compared with the in vivo study.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations